Corrosion-resistant composite material light keel support and preparation method thereof
By combining modified high-density polyethylene and titanium-doped hollow glass microbeads, a light keel bracket of corrosion-resistant composite material was prepared, which solved the problems of flammability, poor stability and insufficient corrosion resistance of existing keel materials, and achieved high strength , toughness and corrosion resistance effects.
Patent Information
- Application Number
- CN202411498081.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
The existing keel materials are flammable, have poor stability, poor strength, are prone to deformation, have poor corrosion resistance, and have short service life.
The combination of modified high-density polyethylene, plasticizer, dispersant, titanium-doped hollow glass beads and flame retardant was used to prepare corrosion-resistant composite light keel brackets through melt grafting reaction and crosslinking reaction.
Without significantly increasing the overall weight, the rigidity, strength and toughness of the material are improved, corrosion resistance and elongation of breaking are enhanced, and service life is extended.
Smart Images

Figure CN119463400A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a corrosion-resistant composite material light keel bracket and a preparation method thereof. Background Art
[0002] Keel is the skeleton and base material of decoration. It is widely used. It is a kind of building material used to support the shape and fix the structure. It is widely used in hotels, terminal buildings, passenger stations, stations, theaters, shopping malls, factories, office buildings, old building renovation, interior decoration settings, ceilings and other places. For example, the roofs of many family rooms or offices now usually need to make suspended ceilings. Suspended ceilings use keels as the internal skeleton of the ceiling. Only with keels can the ceiling be fixed on the top of the house. Keels are also used more in the skeleton of building partition walls. With the rapid development of my country's national economy and the substantial improvement of people's living standards, a large number of high-rise buildings have emerged. These buildings are generally frame-type. One advantage of this frame structure is that it is easy to separate different indoor spaces according to needs. When separating these indoor spaces, many of them are realized by using partition walls, and keels are used as the skeleton inside the partition walls to fix the wall panels; not only that, keels have many other uses, such as aggregates for making furniture, etc.
[0003] Metal keels, wooden keels, aluminum alloy keels, etc. are usually used in building interior and exterior walls, house ceilings, and decorative panel installation projects. These materials are flammable, have poor stability, poor strength, easy deformation, short life, or high manufacturing costs. In addition, metal keels have poor corrosion resistance, are easily corroded, and have a short service life.
[0004] When preparing existing polymer keels, high-density polyethylene is used as the matrix. High-density polyethylene is used as the base resin, which has excellent chemical resistance, electrical insulation and wear resistance. In order to improve the mechanical properties of the material, glass fiber or carbon fiber is usually added. Although the addition of glass fiber or carbon fiber can significantly improve the rigidity, strength and heat resistance of the material, it will also have an adverse effect on the toughness and elongation at break of the material, causing the composite material to be more likely to break after reaching a certain stress. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a corrosion-resistant composite material light keel bracket and a preparation method thereof.
[0006] In order to achieve the above-mentioned objectives, in a first aspect, the present invention provides a corrosion-resistant composite light keel bracket, which comprises the following components by weight: 80-90 parts of modified high-density polyethylene, 12-14 parts of plasticizer, 4-5 parts of dispersant, 9-12 parts of titanium-doped hollow glass microspheres and 2-3 parts of flame retardant.
[0007] Furthermore, the preparation method of the modified high-density polyethylene is as follows:
[0008] A1. Take 85 parts of high-density polyethylene, 2 parts of vinyl triethoxysilane, and 1 part of dicumyl peroxide into a single-screw extruder, and perform melt grafting reaction at a temperature of 130-210 ° C for 3-5min, extrude and granulate to obtain a grafted material;
[0009] A2. 75 parts of high-density polyethylene, 2.0 parts of dibutyltin dilaurate and 0.8 parts of antioxidant were placed in a twin-screw extruder, melt grafted at a temperature of 130-180 ° C for 7-10 minutes, extruded and granulated to obtain a catalyst masterbatch;
[0010] A3. Mix 95 parts of the grafted material in step A1 and 5 parts of the catalyst masterbatch in step A2 and put them into an injection molding machine for injection molding into particles. Put the particles into hot water at 80°C and keep them warm for 8h to complete the cross-linking reaction and obtain modified high-density polyethylene.
[0011] Furthermore, the antioxidant is antioxidant 1010.
[0012] Furthermore, the preparation method of the titanium-doped hollow glass microspheres is as follows:
[0013] B1. The dried titanium-doped xerogel particles were ground and sieved in a mortar to obtain sieved titanium-doped xerogel particles of different particle size ranges;
[0014] B2. The titanium-doped xerogel particles after screening in step B1 are placed in a composite high-temperature xerogel microsphere preparation furnace, and the titanium-doped xerogel particles freely fall from the feed zone of the composite high-temperature xerogel microsphere preparation furnace into the high-temperature zone;
[0015] B3. The titanium-doped dry gel particles in step B2 are subjected to heat absorption, encapsulation, foaming, refining and cooling in sequence, and then washed with deionized water to obtain titanium-doped hollow glass microspheres that are precipitated in a collection vessel of a collector.
[0016] Furthermore, in step B2, 1.0 atm heat-conducting gas is introduced into the composite high-temperature dry gel microsphere preparation furnace, and then the temperature in the composite high-temperature dry gel microsphere preparation furnace is increased from 25° C. to 1400° C.
[0017] Furthermore, the dispersant is polyethylene wax.
[0018] Furthermore, the plasticizer is dioctyl adipate.
[0019] Furthermore, the flame retardant is tributyl phosphate.
[0020] In a second aspect, the present invention provides a method for preparing a corrosion-resistant composite light keel bracket, comprising the following steps:
[0021] S1. By weight, 80-90 parts of modified high-density polyethylene, 12-14 parts of plasticizer, 4-5 parts of dispersant, 9-12 parts of titanium-doped hollow glass microspheres and 2-3 parts of flame retardant are mixed evenly, the mixing temperature reaches 165-175 ° C, and the blend is obtained by mixing;
[0022] S2. The blend of step S1 is conveyed to a twin-screw extruder and granulated at an operating temperature of 165-175 ° C to obtain a composite material;
[0023] S3. The composite material obtained in step S2 is fed into an injection molding machine, melted at 165-175° C., injected into a mold, and cooled to obtain a corrosion-resistant composite light keel bracket.
[0024] This application has the following beneficial effects:
[0025] 1. The titanium-doped hollow glass microspheres of the present invention have a hollow structure inside and a hard titanium-doped glass shell outside. They are a lightweight, high-strength material that meets the requirements of lightweight composite materials. When the titanium-doped hollow glass microspheres are mixed with modified high-density polyethylene with a three-dimensional mesh structure, the titanium-doped hollow glass microspheres are evenly distributed in the modified high-density polyethylene matrix, and the titanium-doped hollow glass microspheres and the modified high-density polyethylene are combined through physical / chemical effects. Without significantly increasing the overall weight of the corrosion-resistant composite light keel bracket, the titanium-doped hollow glass microspheres and the modified high-density polyethylene work together to improve the rigidity and strength of the material.
[0026] 2. The presence of the titanium-doped hollow glass microspheres of the present invention acts as a stress concentration point, which helps to absorb and disperse the externally applied force. The titanium-doped hollow glass microspheres and the modified high-density polyethylene form a stable composite material system through interface bonding. When subjected to external forces, the interface can effectively transfer stress, allowing the two materials to bear the load together, thereby improving the overall toughness and elongation at break. When the composite material is impacted or stretched, microcracks first occur in the more fragile areas. Due to the presence of the titanium-doped hollow glass microspheres, these microcracks will encounter obstacles during the expansion process, thereby slowing down the crack expansion rate and improving the fracture toughness of the material.
[0027] 3. The molecular chains of the modified high-density polyethylene of the present invention present a three-dimensional network structure, which limits the movement of the molecular chains, reduces the free volume inside the material, and reduces the penetration rate and diffusion coefficient of corrosive media (such as acids, alkalis, salts, etc.). The cross-linking points serve as a physical barrier to block or slow down the reaction between corrosive substances and the high-density polyethylene matrix, thereby improving the corrosion resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a trend chart comparing the test data of mechanical properties (elongation at break) of the products obtained in Examples 1-5 of the present invention and Comparative Examples 1-5;
[0029] Figure 2 It is a trend chart comparing the test data of mechanical properties (shear stiffness) of the products obtained in Examples 1-5 of the present invention and Comparative Examples 1-5;
[0030] Figure 3 It is a trend chart comparing the test data of mechanical properties (impact strength) of the products obtained in Examples 1-5 of the present invention and Comparative Examples 1-5;
[0031] Figure 4 This is a trend chart comparing the corrosion resistance (loss rate) test data of the products obtained from Examples 1-5 of the present invention and Comparative Examples 1-5. DETAILED DESCRIPTION
[0032] The present application is further described in detail below in conjunction with embodiments.
[0033] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0034] Example 1: The preparation method of modified high-density polyethylene is as follows: A1. 85 parts of high-density polyethylene, 2 parts of vinyl triethoxysilane and 1 part of dicumyl peroxide are put into a single-screw extruder by weight, and melt-grafted for 3 minutes at a temperature of 130-210°C, extruded and granulated to obtain a grafted material. Specifically, the eight zones of the single-screw extruder are set to 130°C, 170°C, 180°C, 200°C, 210°C, 190°C, 180°C, and 180°C, respectively.
[0035] A2. Take 75 parts of high-density polyethylene, 2.0 parts of dibutyltin dilaurate and 0.8 parts of antioxidant 1010 and put them into a twin-screw extruder, carry out melt grafting reaction at a temperature of 130-180°C for 7 minutes, extrude and granulate to obtain a catalyst masterbatch. Specifically, the nine temperature zones of the twin-screw extruder are set to 130°C, 140°C, 160°C, 170°C, 180°C, 180°C, 170°C, 150°C, and 150°C.
[0036] A3. Mix 95 parts of the grafted material obtained in step A1 and 5 parts of the catalyst masterbatch obtained in step A2 by weight, put them into an injection molding machine for injection molding into particles, and keep the particles in hot water at 80°C for 8 hours to complete the cross-linking reaction, thereby obtaining modified high-density polyethylene.
[0037] The high-density polyethylene used in the above study is 0.948 g / m 3high-density polyethylene; vinyl triethoxysilane was A-151 from Nanjing Youpu Chemical Co., Ltd., diisopropylbenzene peroxide was diisopropylbenzene peroxide from Nouryon, dibutyltin dilaurate was purchased from Beijing Chemical Plant No. 3, and antioxidant 1010 was purchased from Shanghai Lingrui Chemical Co., Ltd.
[0038] The preparation method of titanium-doped hollow glass microspheres is as follows: B1. Grind and sieve the dried titanium-doped xerogel particles in a mortar to obtain titanium-doped xerogel particles of different particle size ranges; use sieves with pore sizes of 235μm and 212μm to sieve the titanium-doped xerogel particles of different particle sizes to obtain a particle size range of 212-234μm.
[0039] Titanium-doped xerogel particles
[0040] A titanium-containing dry gel block of 6.6L i2O·14.9Na2O·5.3K2O·3.7TiO2·1.7B2O3·67.8SiO2 (wt.%) was used as raw material.
[0041] B2. Place the titanium-doped dry gel particles with a particle size range of 212-234 μm in step B1 into a composite high-temperature dry gel microsphere preparation furnace, and the titanium-doped dry gel particles enter the high-temperature zone of the composite high-temperature dry gel microsphere preparation furnace from the feeding zone and fall freely; introduce 1.0 atm of heat-conducting gas into the composite high-temperature dry gel microsphere preparation furnace, and then increase the temperature in the composite high-temperature dry gel microsphere preparation furnace from room temperature to 1400°C.
[0042] B3. After the titanium-doped xerogel particles in step 2 are subjected to heat absorption, encapsulation, foaming, refining and cooling in sequence, and then washed with deionized water, the obtained titanium-doped hollow glass microspheres are precipitated in a collection vessel of a collector. The wall thickness of the titanium-doped hollow glass microspheres is between 1-3 μm and the diameter is between 300-500 μm.
[0043] A method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0044] S1. By weight, 80 parts of modified high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant, 9 parts of titanium-doped hollow glass microspheres and 2 parts of flame retardant are mixed evenly, the mixing temperature reaches 165°C, the mixing time is 30 minutes, and a blend is obtained.
[0045] Among them, the dispersant is polyethylene wax powder, purchased from Guangzhou Ou Ying New Materials Co., Ltd. The plasticizer is dioctyl adipate (industrial grade), purchased from Shandong Yuke Chemical Co., Ltd. The flame retardant is tributyl phosphate, purchased from Jinan Century Tongda Chemical Co., Ltd.
[0046] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0047] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0048] Example 2: The difference between this example and Example 1 is that the proportions of the raw material components of a corrosion-resistant composite material lightweight keel bracket are different.
[0049] The details are as follows: A corrosion-resistant composite lightweight keel bracket, comprising the following components, by weight: 90 parts of modified high-density polyethylene, 14 parts of plasticizer, 5 parts of dispersant, 12 parts of titanium-doped hollow glass microspheres and 3 parts of flame retardant.
[0050] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0051] S1. According to the weight proportions, 90 parts of modified high-density polyethylene, 14 parts of plasticizer, 5 parts of dispersant, 12 parts of titanium-doped hollow glass microspheres and 3 parts of flame retardant are mixed evenly, the banburying temperature reaches 165°C, the banburying time is 30 minutes, and a blend is obtained.
[0052] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0053] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0054] Example 3: The difference between this example and Example 1 is that the proportions of the raw material components of a corrosion-resistant composite material lightweight keel bracket are different.
[0055] The details are as follows: A corrosion-resistant composite lightweight keel bracket, comprising the following components, by weight: 85 parts of modified high-density polyethylene, 13 parts of plasticizer, 4 parts of dispersant, 11 parts of titanium-doped hollow glass microspheres and 2.5 parts of flame retardant.
[0056] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0057] S1. By weight, 85 parts of modified high-density polyethylene, 13 parts of plasticizer, 4 parts of dispersant, 11 parts of titanium-doped hollow glass microspheres and 2.5 parts of flame retardant are mixed evenly, the mixing temperature reaches 165°C, the mixing time is 30 minutes, and a blend is obtained.
[0058] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0059] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0060] Example 4: The difference between this example and Example 1 is that the proportions of the raw material components of a corrosion-resistant composite material lightweight keel bracket are different.
[0061] The details are as follows: A corrosion-resistant composite lightweight keel bracket, comprising the following components, by weight: 88 parts of modified high-density polyethylene, 12.5 parts of plasticizer, 4.5 parts of dispersant, 11 parts of titanium-doped hollow glass microspheres and 2.5 parts of flame retardant.
[0062] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0063] S1. By weight, 88 parts of modified high-density polyethylene, 12.5 parts of plasticizer, 4.5 parts of dispersant, 11 parts of titanium-doped hollow glass microspheres and 2.5 parts of flame retardant are mixed evenly, the mixing temperature reaches 165°C, the mixing time is 30 minutes, and a blend is obtained.
[0064] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0065] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0066] Example 5: The difference between this example and Example 1 is that the proportions of the raw material components of a corrosion-resistant composite material lightweight keel bracket are different.
[0067] The details are as follows: A corrosion-resistant composite lightweight keel bracket, which includes the following components by weight: 90 parts of modified high-density polyethylene, 12 parts of plasticizer, 4 parts of dispersant, 12 parts of titanium-doped hollow glass microspheres and 2.5 parts of flame retardant.
[0068] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0069] S1. According to the weight proportions, 90 parts of modified high-density polyethylene, 12 parts of plasticizer, 4 parts of dispersant, 12 parts of titanium-doped hollow glass microspheres and 2.5 parts of flame retardant are mixed evenly, the banburying temperature reaches 165°C, the banburying time is 30 minutes, and a blend is obtained.
[0070] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0071] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0072] Comparative Example 1: The difference between this comparative example and Example 1 is that the modified high-density polyethylene is replaced by high-density polyethylene.
[0073] The details are as follows: A corrosion-resistant composite lightweight keel bracket, comprising the following components, by weight: 80 parts of high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant, 9 parts of titanium-doped hollow glass microspheres and 2 parts of flame retardant.
[0074] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0075] S1. According to the weight percentage, 80 parts of high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant, 9 parts of titanium-doped hollow glass microspheres and 2 parts of flame retardant are mixed evenly, the mixing temperature reaches 165°C, the mixing time is 30 minutes, and a blend is obtained.
[0076] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0077] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0078] Comparative Example 2: The difference between this comparative example and Example 1 is that the titanium-doped hollow glass microspheres are replaced by hollow glass microspheres.
[0079] The details are as follows: A corrosion-resistant composite light keel bracket, comprising the following components by weight: 80 parts of modified high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant, 9 parts of hollow glass microspheres and 2 parts of flame retardant.
[0080] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0081] S1. According to the weight percentage, 80 parts of modified high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant, 9 parts of hollow glass microspheres and 2 parts of flame retardant are mixed evenly, the mixing temperature reaches 165°C, the mixing time is 30 minutes, and a blend is obtained.
[0082] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0083] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0084] Comparative Example 3: The difference between this comparative example and Example 1 is that the titanium-doped hollow glass microspheres are replaced by glass fibers.
[0085] The details are as follows: A corrosion-resistant composite light keel bracket, calculated by weight, includes the following components: 80 parts of modified high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant, 9 parts of glass fiber and 2 parts of flame retardant.
[0086] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0087] S1. By weight, 80 parts of modified high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant, 9 parts of glass fiber and 2 parts of flame retardant are mixed evenly, the mixing temperature reaches 165°C, the mixing time is 30 minutes, and a blend is obtained.
[0088] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0089] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0090] Comparative Example 4: The difference between this comparative example and Example 1 is that the titanium-doped hollow glass microspheres are deleted.
[0091] The details are as follows: A corrosion-resistant composite light keel bracket, comprising the following components by weight: 80 parts of modified high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant and 2 parts of flame retardant.
[0092] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0093] S1. By weight, 80 parts of modified high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant and 2 parts of flame retardant are mixed evenly, the mixing temperature reaches 165°C, the mixing time is 30 minutes, and a blend is obtained.
[0094] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0095] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0096] Comparative Example 5: The difference between this comparative example and Example 1 is that the modified high-density polyethylene is replaced by high-density polyethylene, and the titanium-doped hollow glass microspheres are deleted.
[0097] The details are as follows: A corrosion-resistant composite light keel bracket, comprising the following components by weight: 80 parts of high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant and 2 parts of flame retardant.
[0098] That is, a method for preparing a corrosion-resistant composite material lightweight keel bracket comprises the following steps:
[0099] S1. According to weight percentage, 80 parts of high-density polyethylene, 12 parts of plasticizer, 4.5 parts of dispersant and 2 parts of flame retardant are mixed evenly, the mixing temperature reaches 165°C, the mixing time is 30 minutes, and a blend is obtained.
[0100] S2. conveying the blend obtained in step S1 to a twin-screw extruder and granulating the blend at a working temperature of 165-175° C. to obtain a composite material. Specifically, the nine temperature zones of the twin-screw extruder are set to 165° C., 165° C., 170° C., 170° C., 175° C., 175° C., 175° C., 170° C., and 165° C., respectively.
[0101] S3, sending the composite material obtained in step S2 into an injection molding machine, melting it at 165° C., injecting it into a mold, and cooling it to obtain a corrosion-resistant composite material light keel bracket.
[0102] Test example: Test items and basis: Elongation at break - GB / T 10654-2001: Elongation at break can be calculated by the formula e=(La-L0) / L0×100%, where La is the length of the sample when it is broken and L0 is the original length of the sample.
[0103] Shear stiffness-GB / T 3354-2014.
[0104] Impact strength-GB / T 1843-2008.
[0105] Corrosion resistance - 80wt% sulfuric acid was used as the soaking liquid to soak the composite samples for 24 hours. The tensile strength of the composite samples before and after soaking was tested, and the corrosion resistance was compared by calculating the loss rate.
[0106] Loss rate (%) = [(tensile strength of unsoaked sample - tensile strength of soaked sample) / tensile strength of unsoaked sample] x 100%.
[0107] Table 1 Test data of test example
[0108]
[0109] Result analysis: From Examples 1-5 combined with Table 1 and Figures 1 to 4 It can be seen that the product prepared by the present invention has excellent mechanical properties and corrosion resistance. The elongation at break is as high as 6.3% or more, the shear stiffness is as high as 243MPa or more, the impact strength is as high as 163KJ / ㎡ or more, and the tensile strength loss rate before and after immersion in 80wt% sulfuric acid for 24 hours is as low as 4.1% or less.
[0110] By combining the data in Table 1 and Example 1, Figures 1 to 4It can be seen that compared with high-density polyethylene, the addition of modified high-density polyethylene can improve the mechanical properties (elongation at break, shear stiffness, impact strength) and corrosion resistance of the obtained products.
[0111] From Example 1, Comparative Examples 2-4 and Table 1 and Figures 1 to 4 It can be seen that the addition of glass fiber can improve the mechanical properties (shear stiffness, impact strength) and corrosion resistance of the product, but the elongation at break will be reduced. Replacing the glass fiber with hollow glass microspheres can further improve the mechanical properties (elongation at break, shear stiffness, impact strength) and corrosion resistance of the product. Replacing the hollow glass microspheres with the titanium-doped hollow glass microspheres of the present invention can further improve the mechanical properties (elongation at break / , shear stiffness, impact strength) and corrosion resistance of the product.
[0112] According to Example 1, Comparative Example 1, Comparative Example 4 and Comparative Example 5 and combined with the data in Table 1 and Figures 1 to 4 It can be seen that there is a synergistic effect between the titanium-doped hollow glass microspheres and the modified high-density polyethylene of the present invention, which can synergistically improve the mechanical properties (elongation at break, shear stiffness, impact strength) and corrosion resistance of the prepared product.
[0113] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0114] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A corrosion-resistant composite light keel bracket, characterized in that: The invention comprises the following components by weight: 80-90 parts of modified high-density polyethylene, 12-14 parts of plasticizer, 4-5 parts of dispersant, 9-12 parts of titanium-doped hollow glass microspheres and 2-3 parts of flame retardant.
2. The corrosion-resistant composite light keel bracket according to claim 1, characterized in that: The preparation method of the modified high-density polyethylene is as follows: A1. Take 85 parts of high-density polyethylene, 2 parts of vinyl triethoxysilane and 1 part of dicumyl peroxide by weight, put them into a single-screw extruder, carry out melt grafting reaction at 130-210° C. for 3-5 minutes, extrude and granulate to obtain a grafted material; A2. Take 75 parts of high-density polyethylene, 2.0 parts of dibutyltin dilaurate and 0.8 parts of antioxidant by weight, put them into a twin-screw extruder, carry out melt grafting reaction at 130-180°C for 7-10 minutes, extrude and granulate to obtain a catalyst masterbatch; A3. Mix 95 parts of the grafted material obtained from A1 and 5 parts of the catalyst masterbatch obtained from A2 by weight, put them into an injection molding machine for injection molding into pellets, put the pellets into hot water at 80°C and keep them warm for 8 hours to obtain modified high-density polyethylene.
3. The corrosion-resistant composite light keel bracket according to claim 2, characterized in that: The antioxidant is antioxidant 1010.
4. The corrosion-resistant composite light keel bracket according to claim 1, characterized in that: The preparation method of the titanium-doped hollow glass microspheres is as follows: B1, grinding and sieving the dried titanium-doped xerogel particles in a mortar; B2, placing the sieved titanium-doped xerogel particles obtained in B1 into a composite high-temperature xerogel microsphere preparation furnace, and allowing them to freely fall from the feed zone into the high-temperature zone; The titanium-doped dry gel particles treated by B3 and B2 are subjected to heat absorption, encapsulation, foaming, refining and cooling in sequence, and then washed with deionized water to obtain titanium-doped hollow glass microspheres.
5. The corrosion-resistant composite light keel bracket according to claim 4, characterized in that: In B2, 1.0 atm heat-conducting gas is introduced into the composite high-temperature dry gel microsphere preparation furnace, and then the temperature in the composite high-temperature dry gel microsphere preparation furnace is increased from 25°C to 1400°C.
6. The corrosion-resistant composite light keel bracket according to claim 1, characterized in that: The dispersant is polyethylene wax.
7. The corrosion-resistant composite light keel bracket according to claim 1, characterized in that: The plasticizer is dioctyl adipate.
8. The corrosion-resistant composite light keel bracket according to claim 1, characterized in that: The flame retardant is tributyl phosphate.
9. A method for preparing a corrosion-resistant composite light keel bracket according to any one of claims 1 to 8, characterized in that: The steps include: S1. Evenly mix the modified high-density polyethylene, plasticizer, dispersant, titanium-doped hollow glass microspheres and flame retardant, and mix at a mixing temperature of 165-175° C. to obtain a blend; S2, conveying the blend obtained in S1 to a twin-screw extruder, and granulating at a working temperature of 165-175° C. to obtain a composite material; S3. The composite material obtained in S2 is fed into an injection molding machine, melted at 165-175° C., injected into a mold, and cooled to obtain a corrosion-resistant composite light keel bracket.